2019
DOI: 10.3390/su11072040
|View full text |Cite
|
Sign up to set email alerts
|

Design and Performance Characterization of Roadside Bioretention Systems

Abstract: In the current study, three roadside bioretention systems with different configurations were constructed to investigate their pollutant removal efficiency in different rainfall recurrence intervals. The bioretention systems (referred as units) (unit A: 700 mm height material without submerged zone; unit B: 400 mm height material with 300 mm submerged zone; unit C: 400 mm height material without submerged zone) were used to conduct the rainfall events with uniform 120 min rainfall duration for 2-, 5-, 10-, 15-,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
(44 reference statements)
1
7
0
Order By: Relevance
“…Current findings for NH 4 + -N and TP are showing the similar trend with the results of Singh et al [34] who demonstrated that NH 4 + -N and TP have good removal effects. Davis et al [35] used sand as a filler to remove nitrogen and phosphorus pollutants from runoff by bioretention systems, which was a stated better removal rate of TP.…”
Section: Water Quality Effect Of Each Structural Layersupporting
confidence: 88%
“…Current findings for NH 4 + -N and TP are showing the similar trend with the results of Singh et al [34] who demonstrated that NH 4 + -N and TP have good removal effects. Davis et al [35] used sand as a filler to remove nitrogen and phosphorus pollutants from runoff by bioretention systems, which was a stated better removal rate of TP.…”
Section: Water Quality Effect Of Each Structural Layersupporting
confidence: 88%
“…Recently, different enhancement methods have been applied to achieve good nitrogen removal (Ali et al 2021;Takaijudin et al 2016;Luo et al 2020;Poor et al 2018;Singh 2019;You 2019;. Lopez 2016;Jiang et al 2016).…”
Section: Fig 2 Traditional Bioretention Systemmentioning
confidence: 99%
“…A lacking denitrification process results in nitrogen removal being unstable and widely variable in the bioretention system, particularly for nitrate (NO 3 ). Nitrogen removal is considered the main challenge encountered by bioretention designers [39][40][41]. Davis et al [30] conducted a laboratory study on the performance of traditional bioretention systems on nutrient removal.…”
Section: Overview Of Bioretention Systemmentioning
confidence: 99%